Pengenalan Peripheral Komputer di SMPN 3 Rancakalong - Nugraha, Muhamad Fahmi (Jurnal AbdiMU (Pengabdian kepada Masyarakat), 2024)
This community service activity aims to increase and also increase student knowledge about computers in an effort to increase student interest. This activity was carried out at SMPN 3 Rancakalong, Sumedang, West Java. The problem that needs to be resolved is that some students are not too familiar with computer components, both hardware and software, because they do not understand computer components in the learning process. The method that will be used in this community service activity is discussion and through questions and answers along with quizzes with prizes so that students are more enthusiastic in the process of learning material about computers. The discussion presented was a theory about the introduction of hardware and software. Training is carried out jointly with students. Through the implementation of this community service activity, it is hoped that there will be many benefits for students at SMPN 3 Rancakalong in increasing their understanding of the functions of hardware and software. The results of this community service activity, namely through the introduction of hardware and software, open students' views about the importance of learning in the field of computers that can help and facilitate solving problems that exist in everyday life.